ASSESSING FLIPPED CLASSROOM IN FLEXIBLE LEARNING VIA COMMUNITY OF INQUIRY FRAMEWORK - Roaima Lynn Bonifacio Antonio (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
Educational institutions adopted online distance learning to ensure continuity of education during the COVID-19 pandemic. The idea of online distance learning was not welcome by some stakeholders for a variety of reasons such as poor internet connection particularly in rural areas, and lack of technological devices to support learning and teaching. Compared to traditional face-to-face delivery, studies show that online distance learning needs new teaching strategies and approaches. One teaching approach that has been seen beneficial to students with limited resources in attending online classes is the use of flipped classroom pedagogy. This study aimed to assess the flipped classroom pedagogy in flexible learning modality using the Community of Inquiry (CoI). It further tried to identify the different issues and challenges of students in using this teaching approach in the context of the pandemic. The descriptive research design was utilized to attain the goal of this study. Using the purposive sampling technique, respondents were selected from two identified cohort classes employing the flipped classroom pedagogy. The findings show that teaching presence, social presence, and cognitive presence are observed in the flipped classroom pedagogy. In addition, the study identified advantages of the flipped classroom pedagogy in online distance learning during the pandemic. As perceived by the respondents, the flipped classroom (1) provides flexibility and convenience to students, (2) addresses the problem of students on internet connectivity and access to technological devices, and (3) offers heightened reinforcement. The study further identified two issues of flipped classroom as observed by the students. These are (1) needed interaction during asynchronous lecture, and (2) limited time for synchronous meetings. Results are futher discussed as well as the implications for future research.